A Smart SCADA System for Oil Refineries - Al-Fadhl, M. (2018)
This paper proposes a smart automated scheme to monitor and control various processes in oil refineries. The proposal aims to continuously collect data from oil tanks and pipelines, trigger alarm systems for any malfunction, apply effective solutions to the corresponding faults, in addition to other smart features that are integrated into the system to optimize its performance. The proposed design is implemented using LabVIEW, while the wireless data acquisition is made using LabJack. The results demonstrate a successful integration between control and monitoring for providing real-time, continuous and accurate in-formation about the status of the oil tanks and pipelines in the field. The proposed design proves to be a smart version of the well-known Supervisory Control and Data Acquisition systems. Extensions to other industrial processes that include pressure, heat, flow, oil level, and gas leakage, via installing dedicated sensors, are also investigated. A friendly graphical user interface and a mobile application are introduced to save the log files for the history of data and to provide means of remotely monitoring and controlling the sensors and actuators.